Poverty and Food Insecurity in the Brazilian Rural: evidence for Rio Grande do Sul from an analysis of the Entitlements (Revista Justiça do Direito, 2019)
Entitlements, present in the rural area of Rio Grande do Sul, associated with the presence of family farming; wealth or the initial allocation of factors; territorial integration; demographic factors and access to education, together, contribute to the reduction of food insecurity in Rio Grande do Sul. Especially in rural areas, promoting a differentiated situation when compared to the Brazilian case, and which make it possible to alleviate situations of food insecurity in the rural area of this state, aiming to promote food security, promoting the development of capabilities of social agents, expanding the role of the agent of the individual, as a member of the public space and as a participant in economic, political and social actions.